1992
DOI: 10.1111/j.1570-7458.1992.tb00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of sunflower volatiles by the red sunflower seed weevil

Abstract: Five principle monoterpenoid and other constituent volatile chemicals of sunflower heads were combined to resemble two lines of sunflower (Helianthus annuus L.): one U.S.D.A. standard line and one French line which was ‘poorly visited by insects’ (Etievant et al., 1984). Field trials of attraction to red sunflower seed weevils (Smicronyx fulvus Le Conte, Coleoptera: Curculionidae) showed that one was clearly preferred over the other. The more attractive mixture contained α‐pinene, β‐pinene, limonene, camphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In order for this to be the case, the beetles must be able to recognize host age via long-distance and/or contact signals. Host plant selection is to a large extent guided by phytochemistry [32,33], where volatile chemicals can strongly affect host plant recognition over long distances [34][35][36] and contact compounds such as plant surface waxes can play an important role in host choice once the insect has come into direct contact with the plant tissue surface [32,33,[37][38][39]. Although other chemicals may also affect host plant choice [40,41], cuticular waxes are the primary chemicals encountered and have been shown to be critical in directing insect behaviour and development [33].…”
Section: Introductionmentioning
confidence: 99%
“…In order for this to be the case, the beetles must be able to recognize host age via long-distance and/or contact signals. Host plant selection is to a large extent guided by phytochemistry [32,33], where volatile chemicals can strongly affect host plant recognition over long distances [34][35][36] and contact compounds such as plant surface waxes can play an important role in host choice once the insect has come into direct contact with the plant tissue surface [32,33,[37][38][39]. Although other chemicals may also affect host plant choice [40,41], cuticular waxes are the primary chemicals encountered and have been shown to be critical in directing insect behaviour and development [33].…”
Section: Introductionmentioning
confidence: 99%
“…The six EAG‐active D. carota volatiles appear to be a unique (and perhaps characteristic) combination in the floral headspace of Daucus spp. α‐Pinene, myrcene, limonene and terpinolene are attractants of bark beetles, α‐pinene and sabinene are suggested to contribute to the attractiveness of certain D. carota cultivars to Trioza apicalis Förster (Homoptera: Psylloidea), whereas α‐pinene, limonene and bornyl acetate are constituents of an attractive blend for Smicronyx fulvus Le Conte (Coleoptera: Curculionidae) …”
Section: Discussionmentioning
confidence: 99%
“…-Pinene, myrcene, limonene and terpinolene are attractants of bark beetles, 44 -pinene and sabinene are suggested to contribute to the attractiveness of certain D. carota cultivars to Trioza apicalis Förster (Homoptera: Psylloidea), 38 whereas -pinene, limonene and bornyl acetate are constituents of an attractive blend for Smicronyx fulvus Le Conte (Coleoptera: Curculionidae). 49 Prior to this study, the few chemical ecology studies on host plant-Bruchinae relationships have primarily focused on larval host plants. [50][51][52] Pouzat 53 demonstrated the EAG activity of the vapour of bean pods, as well as synthetic amyl acetate, in A. obtectus.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that they were attractive to Hylastes ater and Hylurgus ligniperda (Reay and Walsh, 2002). Limonene was attractive to species of the Curculionidae family, such as Hylobius pales (Siegfried, 1987) and Smicronyx fulvus (Roseland et al, 1992). According to Garcia (2010), α-and β-pinene, 3-carene, (S)-cis-verbenol, and (1S)-(−)-verbenone are attractive to males and females of H. ligniperda (Scolitidae).…”
Section: Identification Of Plant Volatile Compoundsmentioning
confidence: 99%